Application of sodium polyacrylate and plant growth-promoting bacterium, Micrococcaceae HW-2, on the growth of plants cultivated in the rooftop. (September 2016) - Hong, Sun Hwa; Ham, Seung Yeon; Kim, Ji Seul; Kim, Im-Soon; Lee, Eun Young
Abstract: This study aimed to evaluate the plant growth-promoting potentials of sodium polyacrylate, a superabsorbent polymer, and Micrococcaceae HW-2, a plant-growth-promoting bacteria. A polymer capable of retaining and continuously supplying moisture was selected and PGPR were isolated from the soil and applied to plants growing in dry environments, such as green rooftops. The moisture absorption and retention abilities of polymer were evaluated at 30 °C and on a rooftop, respectively; the polymer showed water retention potential of 11, 110 times after 480 h and 100 times after 74 h. Strain HW-2 produced 128.95 mg/L indole-3-acetic acid on day 5 of incubation, and ACC deaminase activity was found to be 0.322% after 72 h. Synthesis of siderophores was detected by the formation of an orange halo around the colonies on CAS medium. Application of the mixture of HW-2 and sodium polyacrylate to Arundo donax, a drought-resistant plant, significantly enhanced shoot growth and biomass. Highlights: The effects of the isolated PGPR and selected polymers on plant growth were assessed. Sodium-type superabsorbent polymer (SAP) has excellent water retention potential of 11, 097.93% after 480 h. PGPR, Micrococcaceae HW-2 had activities such as IAA production, ACC deaminase and siderophore-synthesis. Micrococcaceae HW-2 and SAP increased the shoot length, root weight, and biomass of the Arundo donax .